COMPARATIVE STUDY ON STOCK OFFERINGS THROUGH INFORMATION TECHNOLOGY-BASED CROWDFUNDING SERVICES (EQUITY CROWDFUNDING) WITH INITIAL PUBLIC OFFERINGS ACCORDING TO POSITIVE LAW IN INDONESIA - Dewa Ayu Putri Asvini (Jurnal Scientia, 2023)
Technology that has developed rapidly in the last two decades has provided many changes in human life, including investment. Various information technology-based non-bank financial institutions continue to emerge to provide convenience and efficiency for the public. One of the growing fintech products is the crowdfunding system which is the scope of financing. Equity crowdfunding as part of crowdfunding has a concept similar to a public offering that has been run for more than 25 years. Equity Crowdfunding services provide many conveniences for its users, especially new entrepreneurs with limited funds and require additional capital to develop and expand their business. However, the convenience provided is also accompanied by greater risk compared to public offerings on the stock exchange. The research used the Normative Juridical method by examining literature materials: Laws and Regulations, Books, Journals, and Internet Articles related to Equity Crowdfunding and Public Offering. The concept offered by Equity Crowdfunding with Public Offering is similar. Still, the limited services and parties involved provide greater risks such as the risk of investment loss, the risk of lack of liquidity, the risk of scarcity of dividend distribution, and the risk of delusions of share ownership. Moreover, the limited regulation of this service needs to strengthen the existing legal protections to protect its users' rights.